Pengaruh Harga dan Citra Merek terhadap Keputusan Pembelian Air Mineral Gloz Di Bandar Lampung - Nitami Sari; Roslina Roslina; Nuzul Inaz Nabila (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
Changes in every consumer behavior make it necessary for business people to understand consumer behavior precisely and correctly. Building a positive brand image in the minds of consumers will influence purchasing decisions. This type of research in this research is descriptive research and uses quantitative methods. The sample in this study were consumers of Gloz mineral water who made purchases at distributors in the Bandar Lampung area. The population used is unlimited or cannot be measured with certainty, making the researcher choose to use the non-probability sampling method. So that the respondents in this study amounted to 120 people. Based on the results of data processing and analysis, it can be concluded that the price and brand image variables influence the purchasing decision (Y) of Gloz mineral water in Bandar Lampung. The variable that has the greatest influence is the price variable (X1) based on the largest regression coefficient value, namely b1 of 0.249 compared to the regression coefficient value of the brand image variable (X2) of 0.218